Bajo que conceptos se procesa un policia que en determinada situación da de baja a un sujeto con la implementación de la nueva justicia penal militar (2016)
With the formulation of law 1407 of 2010 is intended to set up an idealized structure and designed to give true guidance to criminal investigation and the formation of trials that aim to give meaning to military and police criminal jurisdiction by providing a composition that finds relation with the complex situation that is glimpsed in the delicate issues that arise from the activity of those who belong to the public force, this is understood by the Military Forces (Army, Navy and Air Force) and the National Police. This new reality shows research as the most relevant instrument on which the foundation of the implementation of military and police criminal justice is set up, which together with the implementation of the oral accusatory system, allow for the best competent and independent development of trials and investigations that are presented in the military and police sphere insofar as they allow the best way to achieve the investigation and judgment of those who have the quality and characteristics required by the criminal law for the qualification of the behavior against the commission of a crime, and proof of it can be felt in the delicate situation that arises when a policeman or a military man gives out in combat who is considered at that moment his enemy